Prognostic factors of methotrexate-associated lymphoproliferative disorders associated with rheumatoid arthritis and plausible application of biological agents. Issue 5 (3rd September 2017) - Katsuyama, Takayuki; Sada, Ken-Ei; Yan, Minglu; Zeggar, Sonia; Hiramatsu, Sumie; Miyawaki, Yoshia; Ohashi, Keiji; Morishita, Michiko; Watanabe, Haruki; Katsuyama, Eri; Takano-Narazaki, Mariko; Toyota-Tatebe, Noriko; et al.
Abstract: Objectives: To determine prognostic factors of methotrexate-associated lymphoproliferative disorder (MTX-LPD) and evaluate the efficacy and safety of biological therapy in rheumatoid arthritis (RA) complicated with MTX-LPD. Methods: Thirty RA patients who developed MTX-LPD were investigated in this study. We compared the clinical and laboratory parameters of patients who achieved regression of LPD by MTX withdrawal with those who required chemotherapy and evaluated the clinical course of RA after LPD development. Results: Twenty-three patients (76.7%) achieved regression of LPD by MTX withdrawal. Chemotherapy-free patients had a tendency of shorter RA duration (13.1 vs. 22.0 years, p = 0.108) and higher doses of MTX at LPD diagnosis (8.0 vs. 5.3 mg/w, p = 0.067) than patients who required chemotherapy. A significantly higher positive rate of peripheral blood Epstein–Barr virus (EBV)-DNA was observed in the chemotherapy-free group (9/9 vs. 0/3, p = 0.0002). Of 15 patients that received biological agents after LPD development, 14 patients (93.3%) demonstrated an improved disease activity of RA and persistent remission of LPD, whereas only one patient experienced relapse of LPD during tocilizumab therapy. Conclusions: Peripheral blood EBV-DNA positivity is a potential prognostic marker of better outcome in MTX-LPD. Biological agents could be an option for the treatment of RA patients with MTX-LPD.